AN ANALYSIS OF "OF SEPARATION" POETRY IN THE BOOK OF "THE RING OF THE DOVE" BY IBN HAZM - Azka Syifa Nabilah Syah (TEXTURA, 2021)
Literary work can be defined as the author's imaginative work that describes the reality of people’s lives. To describe that reality, an author usually writes based on personal or others’ experiences. For example, the work of Ibn Hazm namely The Ring of The Dove that written based on his experiences and others’. The aim of this study is to analyze and to know the physical and inner structure of poetry of ‘Of Separation’ by Ibn Hazm and also its connetion with modern Islamic literary work. The method of this study is qualitative descriptive with structuralism approach. The result of this study show that there are: 1) the physical structure of poetry, namely (a) the diction used is simple but accurate to describe the theme, (b) the imagery used are visual and auditory imagery, (c) the concrete words used are very accurate, (d) the figure of speech used includes: simile, hyperbole, personification ; 2) the inner structure of poetry namely (a) the theme of missing and separation, (b) the feeling of sadness, (c) the tone of sorrow, (d) the message of this poetry is we have to treat someone that we love as good as possible unless we will feel sad and regret after the separation ; 3) one of the inner structure of this ‘Of Separation’ poetry, which is the theme that has similarity with the theme of song that called ‘Mencintai Kehilangan’.